Effects of tea oil camellia (Camellia oleifera Abel.) shell-based organic fertilizers on the physicochemical property and microbial community structure of the rhizosphere soil - Huang, Anxiang; Wang, Zhongwei; Yang, Dingyun; Yang, Shoulu; Bai, Wennian; Wu, Nengying; Lu, Xiang; Liu, Zhu (Frontiers in Microbiology, 2023)
Soil microorganisms play important roles in promoting soil ecosystem restoration, but much of the current research has been limited to changes in microbial community structure in general, and little is known regarding the soil physicochemical property and microbial community structure. In this study, four organic fertilizers were first prepared based on tea oil camellia shell (TOCS). Our findings indicate that the application of BOFvo increased both total pore volume and BET surface area of the rhizosphere soils, as well there was a remarkable enhancement in total organic matter (TOM), total nitrogen (TN), available nitrogen (AN), total phosphorus (TP), total potassium (TK), and available potassium (AK) contents of rhizosphere soils. Meanwhile, in comparison to the CK and CF groups, the utilization of BOFvo led to a substantial increase in both average yield and fruiting rate per plant at maturity, as well resulted in a significant increase in TN and TP contents of tea oil camellia leaves. Furthermore, our findings suggest that the application of TOCS-based organic fertilizers significantly enhances the microbial diversity in rhizosphere soils with Proteobacteria and Ascomycota being the dominant bacterial and fungal phyla, respectively, and Rhodanobacter and Fusarium being the dominant bacterial and fungal genus, respectively. Redundancy analysis (RDA) indicates that the physicochemical characteristics of TOCS-based organic fertilizers had a significant impact on the composition and distribution of microbial communities in the rhizosphere soils. This study will facilitate the promotion and application of TOCS-based organic fertilizers, thereby establishing a foundation for the reuse of tea oil camellia waste resources.